Abiotic stresses as tools for metabolites in microalgae. (November 2017) - Paliwal, Chetan; Mitra, Madhusree; Bhayani, Khushbu; Bharadwaj, S.V. Vamsi; Ghosh, Tonmoy; Dubey, Sonam; Mishra, Sandhya
Graphical abstract: Highlights: Abiotic stresses are important tools for metabolites in microalgae. Temperature, nutrient starvation, salinity and light influence PUFAs. Nitrogen and light stress influence phycobiliproteins. Salinity, light and nutrients influence carotenoids. Abstract: Microalgae, due to various environmental stresses, constantly tune their cellular mechanisms to cope with them. The accumulation of the stress metabolites is closely related to the changes occurring in their metabolic pathways. The biosynthesis of metabolites can be triggered by a number of abiotic stresses like temperature, salinity, UV- radiation and nutrient deprivation. Although, microalgae have been considered as an alternative sustainable source for nutraceutical products like pigments and omega-3 polyunsaturated fatty acids (PUFAs) to cater the requirement of emerging human population but inadequate biomass generation makes the process economically impractical. The stress metabolism for carotenoid regulation in green algae is a 2-step metabolism. There are a few major stresses which can influence the formation of phycobiliprotein in cyanobacteria. This review would primarily focus on the cellular level changes under stress conditions and their corresponding effects on lipids (including omega-3 PUFAs), pigments and polymers.